Processing helix–coil transition data: Account of chain length and solvent effects - Yeritsyan, Knarik; Valant, Matjaz; Badasyan, Artem (Frontiers in Nanotechnology, 2022)
Numerous NanoBioTechnologies include manipulations of short polypeptide chains. The conformational properties of these polypeptides are studied in vitro by Circular Dichroism and time-resolved infrared spectroscopy. To find out interaction parameters, the measured temperature dependence of normalized helicity degree needs to be further processed by fitting to a model. Using recent advances in the Hamiltonian formulation of the classical Zimm and Bragg model, we explicitly include chain length and solvent effects in the theoretical description. The expression for the helicity degree we suggest successfully fits the experimental data and provides hydrogen bonding energies and nucleation parameter values within the standards in the field.